SISTEM INFORMASI IT ASSET MANAGEMENT BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER PADA PT. AERO SYSTEMS INDONESIA (ASYST) - Ardiansyah Ardiansyah; Fitria Harnaida (JUST IT : Jurnal Sistem Informasi, Teknologi Informasi dan Komputer, 2017)
End-User Computing (EUC) unit in PT. Aero Systems Indonesia is responsible to handle requests related to the usage of assets for employees, such as computers and printers. Requests are still submitted manually, using paper form. It can only be processed if it has been approved by the supervisor as a condition of usage. Units which had been prepared by EUC team will be submitted with a receipt form. The receipt itself is carbonized paper sheets, which are susceptible to damage (humidity, room temperature, spore) and the potential for loss when mixed with other documents. In addition to the purposes of the documents search that have been stored for a long time becomes difficult because the search must be done manually. To overcome these obstacles, it takes an application for managing employee request related to usage of any assets that will be stored in the form of digital files. This application is in the form of web applications built using CodeIgniter framework and MySQL database. Collaboration framework CodeIgniter and MySQL database will generate dynamic web applications which will generate a form of borrowing and form a receipt and will be storage medium of the form.Key Word : Asset, Form Receive, codeigniter, mysql, web.